Ritual Communication Strategies In Strengthening Hindu Community Social Relations In Mataram City During The Covid-19 Pandemic - I Gusti Komang Kembarawan (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2022)
The Covid-19 pandemic has had a very significant impact on Hindu religious life in the city of Mataram, especially with regard to the implementation of a yajňa ceremony involving the presence of a number of Hindus. This phenomenon affects the social bonds that have been built for a long time. In this regard, in this research, a study was conducted on ritual communication strategies in order to strengthen social solidarity of the Hindu community in Mataram City during the Covid-19 Pandemic. This study was designed in a qualitative descriptive type. The data are presented and analyzed using narrative texts to find answers to the research focus. This study found that there are at least four ritual communication strategies in order to maintain the social ties of the Hindu community. First, intensify communication through social media. Second, to regulate the implementation of religious rituals by complying with health protocols. Third, participating in Hindu religious enlightenment activities online so that it is expected to maintain communication even though it is through a virtual face-to-face process. Fourth, build harmonization of interpersonal communication in the family environment.